A tri-armed boron-based electrolyte and solid-state battery thereof

CN122950609APending Publication Date: 2026-10-20HUZHOU DEJIA ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611163876.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,大多数聚合物电解质(如聚环氧乙烷体系)的电化学稳定窗口较窄,在高电压下易被氧化分解,导致电解质失效和电池容量迅速衰减,尽管有研究尝试引入液态增塑剂或添加剂来提升耐压性,但这又不可避免地牺牲了固态电解质固有的安全性优势,并可能引发界面副反应

Benefits of technology

(1)本发明提供一种三臂硼基电解质及其固态电池,通过在三臂硼基固化剂的分子中心引入具有Lewis酸性的硼原子,硼原子可与电解质中锂盐的阴离子发生相互作用,有效锚定阴离子,从而提高了锂离子的迁移数;使得电池在充放电过程中离子传输更为高效,显著降低了电池的极化程度,使充放电电压平台更加稳定;对比现有技术中液态电解质或普通聚合物电解质存在的阴离子自由移动导致的严重极化和界面不稳定,本案从机理上改善了离子传输的选择性;且由于极化降低和界面稳定性增强,电池在高倍率充放电时仍能保持较好的容量发挥,并有效抑制了循环过程中的容量衰减,从而延长了电池的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of solid-state battery technology and discloses a three-arm boron-based electrolyte and its solid-state battery, comprising a curing agent, an initiator, and a base electrolyte. The curing agent is a three-arm boron-based compound, wherein boron atoms serve as Lewis acid centers for fixing anions, and selectable functional groups R1, R2, and R3 at the ends of the three arms are used to introduce functional groups such as high-voltage resistance or flame retardancy. The electrolyte of this application can significantly improve the lithium-ion transference number, suppress electrode-electrolyte interface side reactions, and enable the solid-state battery to exhibit excellent capacity retention and safety during high-voltage cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and more particularly to a three-arm boron-based electrolyte and its solid-state battery. Background Technology

[0002] Lithium-ion batteries (LIBs) have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage due to their advantages such as high energy density, long cycle life, low self-discharge rate, and wide operating temperature range. However, traditional liquid lithium-ion batteries have inherent safety hazards, especially in large-scale energy storage applications such as electric vehicles and electronic devices, where the safety issues caused by flammable and volatile organic liquid electrolytes are particularly prominent. Furthermore, the energy density of commercial lithium-ion batteries using liquid electrolytes and carbon-based anodes has approached its theoretical limit, restricting further development.

[0003] To address these issues, researchers have begun exploring solid-state electrolytes (SSEs). Due to their high safety and potentially high energy density, SSEs are considered a core direction for next-generation battery technology. However, the practical application of current polymer-based SSEs still faces many challenges, particularly regarding compatibility with high-voltage cathode materials and the stability of the electrode-electrolyte interface.

[0004] First, in pursuit of high energy density, battery systems are evolving towards higher operating voltages. However, most polymer electrolytes (such as polyethylene oxide systems) have narrow electrochemical stability windows and are easily oxidized and decomposed at high voltages, leading to electrolyte failure and rapid capacity decay. Although some studies have attempted to introduce liquid plasticizers or additives to improve voltage resistance, this inevitably sacrifices the inherent safety advantages of solid electrolytes and may trigger interfacial side reactions.

[0005] Secondly, the severe solid-solid interface problem is particularly prominent in solid-state batteries. On the one hand, rigid contact leads to high interfacial impedance and difficulty in ion transport; on the other hand, unstable interfacial reactions between the electrolyte and the highly active lithium metal anode or high-voltage cathode will continuously consume active lithium and electrolyte, forming an unstable interfacial layer that cannot effectively suppress lithium dendrite growth, thereby affecting the cycle life and safety of the battery.

[0006] Therefore, developing a solid electrolyte structure that can simultaneously achieve high ion transport number, excellent interfacial stability, and intrinsic high voltage tolerance without introducing liquid components has become a bottleneck driving the development of solid-state battery technology. Summary of the Invention

[0007] This invention overcomes the shortcomings of the prior art and provides a three-arm boron-based electrolyte and its solid-state battery, which can simultaneously achieve high ion transport number, excellent interface stability and intrinsic high voltage tolerance without introducing liquid components.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a three-arm boron-based electrolyte, comprising a curing agent, an initiator, and a base electrolyte; wherein the curing agent is a functionalized three-arm boron-based curing agent with the structure shown in formula (I): (I) Where 2≤n≤20, R1, R2, and R3 are selected from one or more of the following structural formulas: ; The mass of the curing agent is 1%-10% of the total mass of the electrolyte.

[0009] In a preferred embodiment of the present invention, the three-arm boron-based curing agent comprises any one of the following structural formulas (I-1) to (I-11): (Ⅰ-1) (Ⅰ-2) (Ⅰ-3) (Ⅰ-4) (Ⅰ-5) (Ⅰ-6) (Ⅰ-7) (Ⅰ-8) (Ⅰ-9) (Ⅰ-10) (Ⅰ-11) In a preferred embodiment of the present invention, the initiator is selected from one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, benzoyl tert-butyl peroxide, aluminum triisopropoxy, aluminum triisobutyltrioxide, boron trifluoride, aluminum chloride, lithium metal, and butyllithium; the mass of the initiator is 0.1%-5% of the total mass of the electrolyte.

[0010] In a preferred embodiment of the present invention, the basic electrolyte comprises a lithium salt and an organic solvent; the lithium salt is selected from lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluoroborate oxalate, lithium bis(oxalate)borate, and lithium perchlorate; the mass of the lithium salt is 5%-20% of the total mass of the electrolyte.

[0011] In a preferred embodiment of the present invention, the organic solvent is selected from one or more of propyl acetate, ethyl propionate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, tetrahydrofuran, 1,2-dimethoxypropane, ethylene glycol dimethyl ether, acetonitrile, succinic anion, and adiponitrile; the mass of the organic solvent is 15%-60% of the total mass of the electrolyte.

[0012] Secondly, this application provides a three-arm boron-based solid-state battery comprising the functionalized three-arm boron-based electrolyte as described in any of the above claims.

[0013] In a preferred embodiment of the present invention, the positive electrode material of the solid-state battery is one or more of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary materials, lithium manganese oxide, and nickel-cobalt-aluminum ternary materials.

[0014] In a preferred embodiment of the present invention, the negative electrode material of the solid-state battery is one or more of lithium metal, sodium metal, graphite, and silicon-carbon materials.

[0015] On the other hand, this application provides a method for preparing a three-arm boron-based solid-state battery as described above, comprising the following steps: mixing the functionalized three-arm boron-based curing agent, initiator and basic electrolyte and injecting the mixture into the battery cell, and allowing it to stand for curing.

[0016] In a preferred embodiment of the present invention, the specific steps include: mixing the functionalized three-arm boron-based curing agent, the initiator, and the base electrolyte, wherein the lithium salt concentration in the base electrolyte is 0.5 M to 1.5 M; the mixing process is carried out under an inert atmosphere; and the standing curing time is 2 h to 48 h.

[0017] This invention addresses the shortcomings of the prior art and has the following beneficial effects: (1) This invention provides a three-arm boron-based electrolyte and its solid-state battery. By introducing boron atoms with Lewis acidity into the molecular center of the three-arm boron-based curing agent, the boron atoms can interact with the anions of lithium salts in the electrolyte, effectively anchoring the anions, thereby increasing the transport number of lithium ions. This makes the ion transport more efficient during the charging and discharging process, significantly reducing the polarization of the battery and making the charging and discharging voltage platform more stable. Compared with the severe polarization and interface instability caused by the free movement of anions in liquid electrolytes or ordinary polymer electrolytes in the prior art, this invention improves the selectivity of ion transport from a mechanistic perspective. Moreover, due to the reduction of polarization and the enhancement of interface stability, the battery can still maintain good capacity performance during high-rate charging and discharging, and effectively suppresses capacity decay during cycling, thereby extending the battery's service life.

[0018] (2) This invention provides a three-arm boron-based electrolyte and its solid-state battery. By selectively introducing specific functional groups at the molecular arm ends of the three-arm boron-based curing agent, such as silicon-containing ring structures introduced to improve oxidation resistance or phosphorus-containing units introduced to impart flame retardancy, the electrolyte performance can be customized and synergistically improved as needed. This modular molecular design allows for precise optimization of the electrolyte formulation according to the specific application scenario of the battery, so that the prepared solid-state battery can withstand higher operating voltages to improve energy density and has intrinsic flame retardant properties to enhance safety. Compared with the problems of poor compatibility, easy migration failure or even mutual interference that may be caused by the physical blending of multiple single functional additives in the prior art, this invention integrates multiple functions into a molecular skeleton through strong chemical bonding, ensuring the stable existence and synergistic effect of functional groups, greatly expanding the application range of the electrolyte system, making it possible to develop next-generation solid-state batteries with both high energy density and high safety, and providing a flexible and reliable material solution to meet different market demands. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Figure 1 The molecular structural formula (I) represents the main structure of the three-armed boron-based curing agent. Figure 2 The molecular structural formulas are for functional groups R1, R2, and R3; Figure 3 All molecular structural formulas of the three-armed boron-based curing agent are (Ⅰ-1) to (Ⅰ-11). Figure 4 The graph shows the cycling performance test results of Example 1 and Comparative Example 1 at 25°C. Figure 5 The charge-discharge curves of Example 1 and Comparative Example 1 at 25°C are shown. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0022] The functionalized three-arm boron-based solid electrolyte of this invention can be used in lithium-ion solid batteries. A lithium-ion battery includes a positive electrode material, a negative electrode material, and a solid electrolyte. Example 1:

[0023] Step 1: Prepare the basic electrolyte: Under an argon protective atmosphere, dissolve lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent of ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1) to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Stir until completely dissolved and seal for later use.

[0024] Step 2: Preparation of electrolyte precursor solution: Take 10.00g of the basic electrolyte from Step 1 above, add 0.53g of the three-arm boron-based curing agent of formula (I) (the amount of curing agent is 5% of the total mass of electrolyte), and then add 0.053g of azobisisobutyronitrile (AIBN, the amount of initiator is 0.5% of the total mass of electrolyte). Stir at room temperature in the dark for 12h until completely dissolved to obtain a uniform and transparent electrolyte precursor solution.

[0025] Step 3, Battery Assembly and Curing: The NCM622 positive electrode sheet was stamped into a 12mm diameter disc and vacuum dried at 120℃ for 12 hours; the lithium foil negative electrode was stamped into a 14mm diameter disc. Under an argon protective atmosphere, the CR2032 button cell was assembled in the following order: negative electrode shell, spring sheet, gasket, lithium foil negative electrode, electrolyte precursor solution, PP separator, NCM622 positive electrode sheet, gasket, and positive electrode shell. 80μL of electrolyte precursor solution was added. After sealing the battery, it was kept at 25℃ for 24 hours to complete in-situ curing, resulting in an NCM622||Li metal solid-state battery.

[0026] Example 2-12: The preparation methods of Examples 2 to 11 are exactly the same as those of Example 1, the only difference being the type of functionalized three-arm boron-based curing agent used, namely, as follows: Figure 3 The molecular structural formulas shown are (I-2) to (I-11); Example 12 uses a curing agent with the structure of formula (I-1), and the battery system is a lithium cobalt oxide (LCO)||graphite full cell.

[0027] Example 13: The preparation method is completely consistent with that of Example 1, with the only difference being that the amount of the three-arm boron-based curing agent of Formula I-1 is 1% of the total mass of the electrolyte, and the amount of the initiator AIBN is 0.1% of the total mass of the electrolyte.

[0028] Example 14: The preparation method is completely consistent with that of Example 1, with the only difference being that the amount of the three-arm boron-based curing agent of Formula I-1 is 10% of the total mass of the electrolyte, and the amount of the initiator AIBN is 0.5% of the total mass of the electrolyte.

[0029] Example 15: The preparation method is completely consistent with that of Example 1, with the only difference being that the amount of the three-arm boron-based curing agent of Formula I-1 is 3% of the total mass of the electrolyte, and the amount of the initiator AIBN is 0.3% of the total mass of the electrolyte.

[0030] Example 16: The preparation method is completely consistent with that of Example 1, with the only difference being that the amount of the three-arm boron-based curing agent of Formula I-1 is 7% of the total mass of the electrolyte, and the amount of the initiator AIBN is 0.5% of the total mass of the electrolyte.

[0031] Example 17: The preparation method is completely consistent with that of Example 1, the only difference being that: benzoyl peroxide (BPO) is used as the initiator, the amount of which is 0.5% of the total mass of the electrolyte, and the curing conditions are adjusted to be constant temperature at 50℃ for 12 hours.

[0032] Example 18: The preparation method is exactly the same as in Example 1, the only difference being that the lithium salt in the basic electrolyte is lithium bisfluorosulfonylimide (LiFSI), and the concentration is still 1.0 mol / L.

[0033] Example 19: The preparation method is completely consistent with that in Example 1, with the only difference being that the mixed solvent of the basic electrolyte is ethylene carbonate / methyl ethyl carbonate / adiponitrile (EC / EMC / SN, volume ratio 4:5:1), and the concentration of lithium salt LiTFSI is 1.0 mol / L.

[0034] Example 20: The preparation method is completely consistent with that of Example 1, with the only difference being that the battery system is an NCM811|| silicon-carbon anode full cell, the silicon content in the silicon-carbon anode is 10%, and the test voltage range is 3.0V~4.4V.

[0035] Comparative Example 1: Comparative Example 1 is a conventional liquid electrolyte battery. The preparation process of Comparative Example 1 is similar to that of Example 1, except that no functionalized three-arm boron-based curing agent or initiator is added in the "electrolyte precursor preparation" step. The battery was assembled directly using a prepared 1.0 M LiTFSI in EC / DMC (1:1, v / v) liquid base electrolyte. After adding an equal volume (80 μL) of liquid electrolyte, the battery was immediately sealed without a static curing step, resulting in a medium-nickel ternary / lithium full battery.

[0036] Comparative Example 2: Comparative Example 2 used a commercial polymer electrolyte battery, with polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as the electrolyte matrix. The specific preparation steps were as follows: 1g of PVDF-HFP was dissolved in 10g of N-methylpyrrolidone (NMP), stirred to form a homogeneous slurry, and 0.3g of LiTFSI was added, with stirring continued until homogeneous. This slurry was cast onto a glass plate and dried at 80°C for 12 hours to remove the NMP solvent, yielding a self-supporting polymer electrolyte membrane. During battery assembly, this electrolyte membrane (16mm in diameter) was used to replace the separator in Example 1, and 20μL of liquid electrolyte (1.0 M LiPF6 in EC / DMC) was added for activation. The battery was then sealed to obtain a lithium cobalt oxide / lithium full battery.

[0037] Comparative Example 3: The preparation method is completely consistent with that of Example 1, except that a single-arm linear boron-based compound is used instead of a three-arm boron-based curing agent. The boron atom content and polymerizable double bond content are the same as in Example 1, and the amount of curing agent used is 5% of the total mass of the electrolyte.

[0038] To evaluate the performance of the functionalized three-arm boron-based electrolyte prepared in this invention, electrochemical tests were performed on the batteries assembled in the above examples and comparative examples. All tests were conducted at a constant temperature of 25°C. The test samples were prepared simultaneously with the examples / comparative examples, and the average value was taken from three parallel tests. The test methods are as follows: High-voltage cycle capacity retention testing: All batteries were tested at a constant temperature of 25°C. Constant current charge-discharge tests were performed using a LAND battery testing system. For NCM622||Li metal system batteries (Examples 1-10, Comparative Examples 1-2), the test voltage range was 3.0 V to 4.35 V. For lithium cobalt oxide (LCO)||graphite system batteries (Example 11), the test voltage range was 3.0 V to 4.35 V. All batteries were first subjected to three formatted charge-discharge cycles at a 0.1C rate, followed by a long constant current charge-discharge cycle test at a 0.5C rate, for a total of 200 cycles. The capacity retention rate was calculated as: (Discharge capacity of the 200th cycle / Discharge capacity of the 4th cycle) × 100%.

[0039] Lithium-ion transference number (tLi⁺) test: The steady-state current method was used to test the Li||Li symmetric cell. A constant polarization voltage of 10mV was applied, and the AC impedance and steady-state current before and after polarization were recorded. The lithium-ion transference number was calculated by the Bruce-Vincent formula to directly verify the anchoring effect of boron atoms on anions.

[0040] Interfacial Impedance (EIS) Testing: The AC impedance of the battery before and after cycling was tested using an electrochemical workstation, with a frequency range of 10 Hz. 6 Hz~10 -2 Hz, AC amplitude 5mV, record the interface impedance values ​​before and after cycling to verify the stability of the electrode-electrolyte interface.

[0041] Lithium dendrite suppression performance test: The constant current cycle life of Li||Li symmetric cells at a current density of 0.1 mA / cm² was tested, and the time of voltage polarization abrupt change was recorded to verify the suppression effect of the crosslinking network on lithium dendrites. The test results are shown in Tables 1-4 below: Table 1. Partial formulations and test results of Examples 1-6 Table 2. Partial formulations and test results of Examples 7-12 and Comparative Examples 1-2 Table 3. Partial formulations and test results of Examples 1-12 Table 4. Partial formulations and test results of Examples 13-20 and Comparative Examples 1-3 Results analysis: Based on the above experimental results, we conduct an in-depth analysis of the technical effects and principles of the present invention.

[0042] The test data clearly show that all examples (1-11) using the functionalized three-arm boron-based curing agent of this invention exhibited significantly higher capacity retention rates (93.3% - 95.6%) after 200 cycles at a high voltage of 4.35 V compared to Comparative Example 1 (conventional liquid electrolyte, 74.4%) and Comparative Example 2 (commercial polymer electrolyte, 81.3%). This result verifies the excellent stability of the electrolyte system of this invention under high-voltage conditions. In particular, Example 1 achieved the highest capacity retention rate of 95.6%, demonstrating its significant technical advantages.

[0043] The specific reason is as follows: Functionalized three-arm boron-based curing agent (general structural formula as attached) Figure 1 (I) As shown in the diagram, the unique molecular design firstly involves the boron (B) atom at the center of the curing agent molecule having an empty p orbital, exhibiting Lewis acidity. During battery operation, it can react with the TFSI anion dissociated from lithium salt (LiTFSI). - A strong Lewis acid-base interaction occurs, which effectively anchors the large, slow-migrating anion, thereby significantly increasing the lithium-ion transference number (tLi). + High tLi + This means that lithium ions are the dominant carrier of charge transport, which can significantly reduce the polarization voltage of the battery, improve rate performance, and suppress interfacial side reactions and lithium dendrite growth caused by uneven distribution of anions on the electrode surface.

[0044] As attached Figure 2 As shown, the substituents R1, R2, and R3 at the ends of the three arms can be precisely functionalized. For example, introducing silicon-containing cyclic structures (such as cage-like siloxanes) as high-voltage resistant units can effectively improve the overall antioxidant capacity of the electrolyte, enabling it to withstand high voltages of 4.35V and above. Introducing phosphorus-containing cyclic structures (such as cyclic phosphates) as flame-retardant units endows the electrolyte with intrinsic flame retardancy, improving safety. These functional groups are integrated into a molecule through chemical bonding, achieving functional synergy, which is unmatched by simple physical blending additives.

[0045] Furthermore, under the action of the initiator, the curing agent polymerizes to form a three-dimensional cross-linked network, solidifying the liquid electrolyte into a gel state. This network structure provides excellent mechanical properties, helping to suppress lithium dendrite penetration. Simultaneously, the design of the functionalized arms and the high tLi... + The characteristics of these elements work together to promote the formation of a stable and dense solid electrolyte interphase (SEI / CEI) film on the surfaces of the lithium metal anode and the high-voltage cathode. This effectively protects the electrode materials, reduces the loss of active materials and the increase of interfacial impedance, which is the fundamental reason why the battery can cycle stably for a long time.

[0046] Figure 4The graph clearly shows the performance comparison between the batteries of Example 1 and Comparative Example 1 after 200 cycles at a 0.5C rate and a voltage range of 3.0-4.35V. The vertical axis represents capacity retention (%), and the horizontal axis represents the number of cycles. The results show that Example 1 (black solid dot curve) exhibits extremely excellent cycle stability, with its capacity retention consistently maintained at a high level of over 98% throughout the test, and still well above 98% after 200 cycles. In contrast, the capacity decay of Comparative Example 1 (hollow dot curve) is very significant, dropping sharply from an initial 100% to approximately 73% at 200 cycles. The huge performance gap formed by the two curves intuitively demonstrates that the functionalized three-arm boron-based electrolyte provided by this invention can greatly suppress battery capacity decay at high voltages. The stable decay curve of Example 1 indicates that its internal interface is stable and side reactions are effectively suppressed; while the rapid decay of Comparative Example 1 reveals the instability of traditional liquid electrolytes at high voltages. This graph data is the most direct and powerful evidence that the technical solution of this invention can significantly improve battery cycle life and high-voltage stability.

[0047] Figure 5 The charge-discharge curves of the batteries in Example 1 and Comparative Example 1 during the 2nd and 195th cycles are shown. The relationship between voltage and specific capacity visually demonstrates the performance advantages of the electrolyte of this invention during long-term cycling. Specifically, the two curves of Example 1 in the 2nd and 195th cycles highly overlap, with a stable charge-discharge plateau voltage and minimal specific capacity decay, indicating excellent capacity retention and extremely low polarization growth, and a highly stable electrode-electrolyte interface. In contrast, the two curves of Comparative Example 1 show a clear separation: the discharge plateau voltage in the 195th cycle decreases significantly, while the charging plateau voltage increases, indicating intensified polarization. Simultaneously, the reversible specific capacity also decreases significantly, reflecting severe interfacial side reactions and loss of active material. This comparison fully demonstrates that the functionalized three-arm boron-based electrolyte provided by this invention can effectively suppress interfacial degradation and capacity decay during long-term high-voltage cycling, thereby ensuring its excellent cycle stability.

[0048] Furthermore, as can be seen from Tables 3 and 4, the lithium-ion transference number of all embodiments reached above 0.62, with the optimal embodiment 1 reaching 0.78, which is much higher than that of comparative examples 1-3. This proves that the central boron atom of the present invention acts as the core mechanism for Lewis acid anchoring anions, achieving a significant increase in the lithium-ion transference number and solving the problems of severe polarization and frequent interfacial side reactions caused by anion migration in the prior art.

[0049] Meanwhile, Examples 13-16 cover the full range of curing agent dosage from 1% to 10% in claim 1. Examples with dosages of 1% and 10% at the end of the range achieve technical effects superior to the comparative examples, proving that all technical solutions within this numerical range can achieve the purpose of the invention. Examples 17-19 verify the technical feasibility of different initiators, lithium salts, and organic solvents in claims 3-5, providing complete specification support for the scope of protection of the claims and solving the defect that the claims of the original scheme were not supported.

[0050] Analysis of the interfacial impedance after cycling showed that the interfacial impedance of all embodiments was less than 150Ω, far lower than the 392Ω or more of the comparative example; the Li||Li symmetric battery had a cycle life of up to 1200h, which is more than 6 times that of the comparative example 1, directly proving the stabilizing effect of the cross-linked network structure of the present invention on the electrode-electrolyte interface and the suppression effect on lithium dendrites, providing a direct mechanistic explanation for the improvement of cycling performance.

[0051] In summary, this invention improves upon the shortcomings of solid-state batteries, such as low ion transference number, poor high-voltage compatibility, interface instability, and insufficient safety, through the synergistic effect of "boron-centered anion fixation" and "three-arm functional design".

[0052] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A three-arm boron-based electrolyte, characterized in that, It includes a curing agent, an initiator, and a base electrolyte; the curing agent is a functionalized three-arm boron-based curing agent with the structure shown in formula (I): Equation (I) Where 2≤n≤20, R1, R2, and R3 are selected from one or more of the following structural formulas: ; The mass of the curing agent is 1%-10% of the total mass of the electrolyte.

2. The three-arm boron-based electrolyte and its solid-state battery according to claim 1, characterized in that: The three-arm boron-based curing agent includes any one of the following structural formulas (Ⅰ-1) to (Ⅰ-11): (Ⅰ-1) (Ⅰ-2) (Ⅰ-3) (Ⅰ-4) (Ⅰ-5) (Ⅰ-6) (Ⅰ-7) (Ⅰ-8) (Ⅰ-9) (Ⅰ-10) (Ⅰ-11)。 3. The three-arm boron-based electrolyte and its solid-state battery according to claim 2, characterized in that: The initiator is selected from one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, benzoyl tert-butyl peroxide, aluminum triisopropoxy, aluminum triisobutyltrifluoride, boron trifluoride, aluminum chloride, lithium metal, and butyllithium; the mass of the initiator is 0.1%-5% of the total mass of the electrolyte.

4. The three-arm boron-based electrolyte and its solid-state battery according to claim 3, characterized in that: The basic electrolyte contains a lithium salt and an organic solvent; the lithium salt is selected from one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium oxalate difluoroborate, lithium bis(oxalate)borate, and lithium perchlorate; the mass of the lithium salt is 5%-20% of the total mass of the electrolyte.

5. The three-arm boron-based electrolyte and its solid-state battery according to claim 4, characterized in that: The organic solvent is selected from one or more of propyl acetate, ethyl propionate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, tetrahydrofuran, 1,2-dimethoxypropane, ethylene glycol dimethyl ether, acetonitrile, succinic anhydride, and adiponitrile; the mass of the organic solvent is 15%-60% of the total mass of the electrolyte.

6. A three-arm boron-based solid-state battery, characterized in that, It comprises a functionalized three-arm boron-based electrolyte as described in any one of claims 1-5.

7. The three-arm boron-based solid-state battery according to claim 6, characterized in that, The cathode material of the solid-state battery is one or more of lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary materials, lithium manganese oxide, and nickel-cobalt-aluminum ternary materials.

8. The three-arm boron-based solid-state battery according to claim 6, characterized in that, The negative electrode material of the solid-state battery is one or more of lithium metal, sodium metal, graphite, and silicon-carbon materials.

9. A method for preparing a three-arm boron-based solid-state battery as described in any one of claims 6-8, characterized in that, Includes the following steps: The functionalized three-arm boron-based curing agent, initiator, and base electrolyte are mixed and injected into the battery cell, and then allowed to stand for curing.

10. The method for preparing a three-arm boron-based solid-state battery according to claim 9, characterized in that, Specifically, the following steps are included: The functionalized three-arm boron-based curing agent, initiator, and base electrolyte are mixed, wherein... The lithium salt concentration in the basic electrolyte is from 0.5 M to 1.5 M; The mixing process is carried out under an inert atmosphere. The curing time is 2 hours to 48 hours.